ANALISIS EDUKATIF CERPEN MISI MENYELAMATKAN JANTUNG AYAH KARYA WIDYA AZHARI - Kusuma Yuda, Ramadhan; Fitriani; Salsabila, Aurel Aulia (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the educational value of the short story "Mission to Save Father's Heart" by Widya Azhari as a narrative-based health education medium. The method used is descriptive qualitative with content analysis techniques on the short story text. The analysis focused on identifying and categorizing educational values ​​related to medical knowledge, heart disease prevention, family empathy, and religious values. The results of the study indicate that the short story contains health education messages conveyed through a simple and emotional narrative flow, so that it is able to connect medical information with family experiences. The conclusion of this study states that short stories can be used as an effective health promotion medium because they present health education in a humanistic manner and are easy for readers to understand.